Metamorphosis of public spaces in Hungary or the question of context within the public spaces of the communist and post-communist period - Kissfazekas, Kornelia (Journal of Architecture and Urbanism, 2013)
The design of successful public spaces is not merely a simple stylistic problem, but also a reflection on the social circumstances of a certain era, an architectural answer to the demands of society (Shields 1986). By following the continuous change in public spaces, we can observe a particular slice of history. This study is an investigation of the changing roles of two very different types of public spaces common in Hungary: the new urban squares of the ’50s and the centres built in the ’70s for public institutions. The study accomplishes this primarily by analysing them within their different contexts. The conclusion of this study is that public squares built in the communist period can meet contemporary space use demands in different ways. However these square types’ problems have great differences in scale and nature, during their renewals the deep knowledge of their history is essential. This is the precondition to creation public spaces that are intimately linked to the venue (and its spirit and history), even if we use fashinable designing tools.